2005
DOI: 10.1038/nbt1094
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Agrobacterium tumefaciens–mediated transfection of viral replicons for efficient transient expression in plants

Abstract: Plant biotechnology relies on two approaches for delivery and expression of heterologous genes in plants: stable genetic transformation and transient expression using viral vectors. Although much faster, the transient route is limited by low infectivity of viral vectors carrying average-sized or large genes. We have developed constructs for the efficient delivery of RNA viral vectors as DNA precursors and show here that Agrobacterium-mediated delivery of these constructs results in gene amplification in all ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
404
1
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 478 publications
(422 citation statements)
references
References 22 publications
7
404
1
10
Order By: Relevance
“…Preliminary data in our laboratory indeed suggest that binary ethyleneimine treatment effectively inactivates the protein A-coated viral particles and that the immunoabsorbant properties of the particles are not affected. Other more sophisticated solutions would include the production of particles using technologies that do not require full functionality of the virions, such as magnifection (39). In separate experiments, we (C. Engler, S.W., S.M., and Y.G., unpublished work) and, earlier, others (40,41) have demonstrated that viral replicons and vectors lacking a functional movement protein gene (required for cell-to-cell movement of virus) can be fully complemented by transgenic plant hosts expressing the viral movement protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary data in our laboratory indeed suggest that binary ethyleneimine treatment effectively inactivates the protein A-coated viral particles and that the immunoabsorbant properties of the particles are not affected. Other more sophisticated solutions would include the production of particles using technologies that do not require full functionality of the virions, such as magnifection (39). In separate experiments, we (C. Engler, S.W., S.M., and Y.G., unpublished work) and, earlier, others (40,41) have demonstrated that viral replicons and vectors lacking a functional movement protein gene (required for cell-to-cell movement of virus) can be fully complemented by transgenic plant hosts expressing the viral movement protein.…”
Section: Discussionmentioning
confidence: 99%
“…Viral expression vectors used in this study are based on the TMV-related viruses TVCV (43) and CrTMV (44). The basic principle of proviral expression modules and their optimization for high-level expression was described (18,39). The sequence of the IgG-binding domains E and D from the S. aureus protein A along with short sequences on both sides (amino acids 29-161; GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…Since RNA viruses do not enter the nucleus in its natural life cycle, Icon's vector was elegantly tailored for its artificial nucleus-to cytoplasm passage by addition of introns and removal of cryptic splicing sites [81]. As a result, its performance was significantly improved reaching levels of up to 40% TSP for certain recombinant proteins.…”
Section: Deleted: Alsomentioning
confidence: 99%
“…The pathway leading to the latter alkaloids has been almost completely unravelled at the enzymatic level, which together with a number of side reactions describes a great deal of the Rauvolfia alkaloid metabolism. About half of the enzymes involved in the biosynthesis of ajmaline have previously been functionally overexpressed in Escherichia coli, yeast and more recently developed but highly effective plant expression systems such as Nicotiana benthamiana (Marillonnet et al, 2004(Marillonnet et al, , 2005Ruppert, Woll et al, 2005). Heterologous expression resulted in highly purified protein in milligram quantities suitable for systematic crystallization of the Rauvolfia enzymes and elucidation of their three-dimensional structures.…”
Section: Introductionmentioning
confidence: 99%